Darurat Sampah Nasional di Indonesia: Analisis Pengelolaan Limbah dan Dampaknya terhadap Pencemaran Lingkungan dalam Perspektif Sustainable Development Goals - Condo Leezza Chrismanta; Citra Azra Amalia; Nabila Isyana Putri; Muhammad Zia Ulhaq; Muhammad Adymas Hikal Fikri (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
The waste problem in Indonesia has now reached a critical stage and has become an increasingly serious environmental issue. The ever-increasing volume of waste is not being managed effectively, leading to various negative impacts, particularly environmental pollution. This study aims to examine the state of waste management in Indonesia and its impact on water pollution from the perspective of the Sustainable Development Goals (SDGs). The method used is descriptive qualitative research through a literature review utilizing various sources such as journals, official reports, and legislation. The results indicate that the majority of waste originates from household activities, while management practices remain rudimentary, such as the “collect-transport-dispose” method and open dumping. This situation leads to waste accumulation, which contributes to water pollution, deteriorating environmental quality, and increased health risks for the community. Furthermore, suboptimal waste management also poses a challenge in achieving sustainable development goals, particularly regarding responsible consumption and access to clean water and sanitation. Therefore, improved efforts are needed through the application of the reduce, reuse, recycle (3R) principles, increased public awareness, and the active role of the government and the private sector in providing a sustainable waste management system. With the right measures, it is hoped that the waste problem in Indonesia can be reduced and the environment preserved.